Pengaturan dan Penegakkan Hukum Bagi Tindak PIDAN White Collar Crime - Ivan Prawita; Hilmi Safitri; Sahlan Sahlan (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
White collar crime is a crime committed by people who have a high socio-economic status and have a respected position in society. This white collar crime is very different from conventional crime in general, where the perpetrators are people from a low socio-economic class. Perpetrators of white collar crime include businesspeople, officials and professionals.